REVEALED COMPARATIVE ADVANTAGE (RCA) AND ITS APPLICATION TO EVALUATE INDIA’S PERFORMANCE OF FRESH MANGOES, MANGOSTEEN & GUAVAS DURING THE PERIOD 1991-2020: AN ANALYSIS WITH RESPECT TO TRADE - Shankar, Dr. Sidharth; Kumar, Dr. Govind; Singh, Dr. Abhishek; Mishra, Dr. Pradeep K (The journal of contemporary issues in business and government, 2023)
The international market for fresh fruits and vegetables is truly humongous. And, with countries in Asia experiencing significant addition in the purchasing power of their middle classes, the demand for these, as well as for a host of other agricultural products, is sure to rise exponentially in the future too. From India’s point of view, what makes the prospect even more attractive is the fact, that there aren’t too many countries with the production capacity to meet this ever-expanding demand. Fresh Mangoes, Mangosteens & Guavas represent a particularly promising sub-segment in the larger fresh fruits & vegetables space. In this paper, an attempt has been made to study the production and export performance of India for these products during the period 1991- 2020. Data available in the public domain depicts India as a very large producer of most of the tropical fruits, but proportionately not such a large exporter. This dichotomy has baffled many experts and policy makers for quite some time. In this working paper, an attempt has been made not just to trace the trajectory of India as a producer and as an exporter, but also to analyze the factors that have a bearing on the production of these commodities in India, and export of the same from India. As analytical tools to aid the study, statistical measures such as CAGR, RCA, RSCA, time series method (TSM), correlation & regression, standard deviation, mean and coefficient of deviation have been used in this study to derive meaning out of the various disparate data elements. Finally, this study also tries to identify the areas of weaknesses that require urgent remedial steps. And, the study also makes a few key recommendations to improve India’s performance as a producer and exporter of the two commodities.